Merbabuku: Platform Web untuk Meningkatkan Efisiensi dan Edukasi Pendaki Gunung di Indonesia - Dandi Riski Saputra; Tito Fernando Suprapto; Fahriza Wahyu Akbar; Al Ma'mur Nur Effendi (Lembaga Pengembangan Kinerja Dosen, 2025)
Mountain climbing is gaining popularity, but high risks arise from inadequate preparation and information. Climbers often face limited access to crucial details like verified routes, real-time weather, essential equipment, and structured educational resources. To address this, Merbabuku, a web-based platform, was developed to help climbers plan their trips more efficiently, safely, and informatively. This research focused on designing and developing Merbabuku with features such as verified route information, official weather forecasts (BMKG), climbing tips, equipment checklists, and a community forum. Utilizing the Software Development Life Cycle (SDLC) waterfall model, encompassing analysis, design, implementation, testing, and evaluation, the platform was built using HTML, CSS, JavaScript, PHP, and MySQL. Functional tests confirmed all features worked as intended, and a user satisfaction survey of 50 respondents showed 92% found Merbabuku highly beneficial for planning and gaining insights into safety and ethics. Merbabuku aims to be a digital innovation that not only streamlines information access but also elevates awareness and education on climbing safety and environmental preservation.